2011
DOI: 10.4238/vol10-1gmr1017
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression patterns in the autogamous plant Hordeum euclaston (Poaceae)

Abstract: ABSTRACT. Sib-seedlings of 95 strains of the strictly autogamous grass Hordeum euclaston were analyzed by horizontal polyacrylamide gel electrophoresis for four isoenzyme systems at a specific ontogenetic stage. We found differences in the activity of some genes among individuals of this species. Hence, an ontogenetic analysis was carried out to investigate 12 strains at five ontogenetic stages, to determine the patterns of expression of these genes during development. The differences in the presence versus ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Similar pattern was observed in case of different plants closely related to wheat as: maize [8], rice [9], millet [10], barley [11, 12] or finger millet [13]. Based on the zymographic analyses of AAT preparations from different subcellular fractions of wheat seedlings, it was found that AAT-1 zone (the one with the highest electrophoretic mobility towards the anode) is composed of mitochondrial allozymes, while AAT-2 and AAT-3 zones correspond to plastidial and cytosolic allozymes, respectively [7].…”
Section: Introductionsupporting
confidence: 78%
“…Similar pattern was observed in case of different plants closely related to wheat as: maize [8], rice [9], millet [10], barley [11, 12] or finger millet [13]. Based on the zymographic analyses of AAT preparations from different subcellular fractions of wheat seedlings, it was found that AAT-1 zone (the one with the highest electrophoretic mobility towards the anode) is composed of mitochondrial allozymes, while AAT-2 and AAT-3 zones correspond to plastidial and cytosolic allozymes, respectively [7].…”
Section: Introductionsupporting
confidence: 78%
“…The following gene families have been identified and characterized in Oryza (SnRK2 family) (Saha et al, 2014), Arabidopsis (PYR/RCAR family) (Merilo et al, 2013), and Populus (ABF family) (Ji et al, 2013). Georg-Kraemer et al (2011) analyzed differential gene expression patterns in Hordeum euclaston. Zhou et al (2015) isolated a novel EsMcsu1 gene encoding a molybdenum cofactor from Eutrema salsugineum, which promotes the ABA biosynthesis and increases drought resistance in alfalfa.…”
Section: Introductionmentioning
confidence: 99%